The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.2166/wst.2010.032
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of bioflocculation in a high-loaded membrane bioreactor for improved energy recovery from sewage

Abstract: The feasibility of a high-loaded membrane bioreactor to improve methane recovery from sewage was investigated. Although the process needs further optimization, it already is feasible to recover at least 35% of the sewage COD. Important aspects for further research are the occurrence of membrane fouling, and the optimum process conditions for bioflocculation, i.e. the proper SRT/HRT ratio, dissolved oxygen concentration and shear and overall energy production and consumption under optimised conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 0 publications
4
32
0
Order By: Relevance
“…1). This was in line with earlier studies about HLMBRs (Akanyeti et al 2010;Faust et al 2014a). Enhanced bioflocculation was positively correlated to the increased concentration of sludge-bound EPS at longer SRTs when five HLMBRs were operated at various SRTs between 0.125 and 1 day (Faust et al 2014a).…”
Section: Bioflocculation At Different Srtssupporting
confidence: 91%
See 2 more Smart Citations
“…1). This was in line with earlier studies about HLMBRs (Akanyeti et al 2010;Faust et al 2014a). Enhanced bioflocculation was positively correlated to the increased concentration of sludge-bound EPS at longer SRTs when five HLMBRs were operated at various SRTs between 0.125 and 1 day (Faust et al 2014a).…”
Section: Bioflocculation At Different Srtssupporting
confidence: 91%
“…Flocculation efficiency increased from 49 % in R0.125 to 84 % in R0.5 and to 94 % in R1. This is in line with earlier studies investigating the bioflocculation process in HL-MBRs (Akanyeti et al 2010;Faust et al 2014a). A previous research (Faust et al 2014a) showed that the increase of bioflocculation at longer SRTs was accompanied by higher sludge concentration of bound EPS, and it was concluded that EPS, in particular EPS-proteins, govern the bioflocculation process in HLMBRs.…”
Section: Cod Fractionssupporting
confidence: 90%
See 1 more Smart Citation
“…These characteristics prevent the direct production of valuable resources from organic matter, such as methane or volatile fatty acids (VFA), and makes pre-treatment to concentrate the organic matter necessary. Aerobic bioflocculation of raw sewage in a high-loaded membrane bioreactor (HL-MBR) is a promising technique to accomplish such a concentration step, while at the same time it can produce a water quality that is fit for reuse (Akanyeti et al, 2010;Faust et al, 2014 Often anaerobic digestion is applied to reduce the amount of primary sludge (PS) and secondary activated sludge (AS) and to produce methane from these solids (Lettinga, 1995). This process consists of four subsequent steps: hydrolysis, acidogenesis, acetogenesis and methanogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…This result is in line with the study by Ferreiro and Soto (2003), who found a specific VFA production of 170 -370 mg COD/g VSS of PS and a VFA composition of 37-60% acetate, 30-55% propionate and 8-20% butyrate. Akanyeti et al (2010) reported that with a combination of aerobic bioflocculation and subsequent anaerobic digestion at least 35% of sewage COD can be converted to methane. This yield is much higher than a methane recovery of 18% when PS and/or a mixture of PS and AS are digested (Cao, 2011).…”
Section: Introductionmentioning
confidence: 99%